2011
DOI: 10.1007/s10103-010-0878-6
|View full text |Cite
|
Sign up to set email alerts
|

Porcelain conditioning with Nd:YAG and Er:YAG laser for bracket bonding in orthodontics

Abstract: In this study, shear bond strength (SBS) of metal orthodontic brackets to porcelain following conditioning by Er:YAG (erbium-doped yttrium aluminum garnet) and Nd:YAG (neodymium-doped yttrium aluminum garnet) laser in comparison to conventional methods was evaluated. One hundred glazed porcelain discs with an upper central shape were prepared and randomly assigned to five equal groups of 20. In the first group, samples were only deglazed and roughened by diamond burs. In the second group, after roughening and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 16 publications
2
58
1
1
Order By: Relevance
“…7 A number of alternative methods have been suggested to overcome this problem, such as deglazing and roughening the porcelain surface with a diamond bur, microetching the surface with aluminum oxide particles, conditioning the porcelain surface with the application of silane, and, most recently, lasers. 5,10,13,14,18,[21][22][23][24][25][26] Some of the previous studies [22][23][24][25] have evaluated the effect of Nd:YAG and Er:YAG lasers on porcelain surface treatment for efficient bracket bonding, whereas some other studies 5,26 have assessed the effectiveness of CO 2 laser for this purpose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 A number of alternative methods have been suggested to overcome this problem, such as deglazing and roughening the porcelain surface with a diamond bur, microetching the surface with aluminum oxide particles, conditioning the porcelain surface with the application of silane, and, most recently, lasers. 5,10,13,14,18,[21][22][23][24][25][26] Some of the previous studies [22][23][24][25] have evaluated the effect of Nd:YAG and Er:YAG lasers on porcelain surface treatment for efficient bracket bonding, whereas some other studies 5,26 have assessed the effectiveness of CO 2 laser for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The results on the efficacy of Er:YAG laser in porcelain conditioning is more controversial. 22,24,25 Two studies evaluated the effect of CO 2 laser irradiation of porcelain surfaces on the bond strength of metal orthodontic brackets. 5,26 Akova et al 5 concluded that superpulse CO 2 laser irradiation provided adequate bonding strength between metal brackets and porcelain surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results prove that the 2W/20-second superpulse CO 2 laser irradiation provides acceptable bond strength of metal brackets to porcelain surfaces. Poosti et al 21 proved that laser irradiation by Nd:YAG laser is an acceptable substitute for hydrofluoric acid; however, the Er:YAG laser is not an acceptable option.…”
Section: Treatment By Different Laser Techniquesmentioning
confidence: 99%